Australia : Financial Safety Net and Crisis Management Framework-Technical Note. (IMF Staff Country Reports; Country Report ;, 2012)
Australia has a history of few bank failures, even fewer financial crises, and its banking sector emerged from the global financial crisis relatively well.1 With an eye toward international developments, the Australian authorities have taken commendable steps to strengthen the financial safety net and crisis management framework over the last several years. The Government's well-coordinated response to the global financial crisis included adopting significant legislative changes in October 2008 to put in place guarantee arrangements for retail deposits, among other enhancements to the financial safety net and crisis management framework. Further improvements were made in June 2010 and the Government is currently pursuing additional legislative changes.